THE ROLE OF FINANCIAL TECHNOLOGY IN PROMOTING GROWTH IN ISLAMIC FINANCE IN THE DIGITAL ERA - Putri, Mutiara Eka; Hanif, Hanif (Al Fiddhoh: Journal of Banking, Insurance, and Finance, 2024)
Financial technology (fintech) has increased and can potentially drive Sharia finance's growth. This study aims to analyze fintech's role in promoting Islamic finance's growth in the digital era. The research method uses a literature study. A descriptive analysis approach involves breaking secondary data in journals, articles, and statistical reports related to the research topic. The results of this study indicate that the adoption of fintech in Sharia finance is predicted to continue to increase, driven by the millennial Muslim population. Fintech provides opportunities for Sharia financial product innovation. However, the challenges of developing Sharia fintech are significant and related to regulations, compliance risk, and human resources. Some examples of Sharia fintech platforms, such as P2P lending and equity crowdfunding, have been quite successful. The prospects for sharia fintech in Indonesia are positive with the support of digital infrastructure and the millennial Muslim population. Regulatory support is needed so that Sharia fintech is truly compliant and can drive the growth of Islamic finance. Sharia fintech has the potential to be a game changer for the development of Islamic finance in Indonesia. Comprehensive support from regulators and stakeholders can realize the optimal implementation of Sharia fintech for inclusive and sustainable Sharia finance expansion.